Need to adopt Quranic way of Life in the Modern Era (Al-Qamar, 2024)
In deed this is thought provoking topic when we compare current life style which is quietly different from holy Quran and Islamic teachings while it is not ancient book but it is valid book till the day hereafter because Quran is miracle and implementable till the day of Judgement lot of scientists have benefited by Quran and they also agree up on the excellence of Quran. Hence in this research we have to prove dominancy of Quran over on all other life styles, it is crystal clear that the creator or inventor has right to make the rules and regulations of invented or created thing as compare to others because these are ignorant from the needs and requirement of that thing. Likewise in the life style when we pondering that Almighty Allah has created a humanity He knows the requirement and needs of human beings it is obvious that the Quran is challenges that ‘if you have any doubt in what we have revealed on our servant bring merely chapter of it if you are truthful” it is also real fact that each and every system or thought has to manifesto and let book which called as constitution being Muslim we believe that Islam is complete code of life and the constitution of Islam is Sacred Book Quran if it is then why we follow other life styles other than Quran. Comparatively this time is well advanced period and lot of things invented while concept of these things was present in this sky book, I have drawn intention of readers on these points.
Keywords: Quranic way; Life; Modern Era